Efektivitas Penerapan Video Pembelajaran pada Mata Pelajaran Dasar Listrik Elektronika - Muhammad Faiz Al Hafizh Putra; Mukhlidi Muskhir (Jurnal Pendidikan Teknik Elektro, 2022)
This study aims to find out how effective the use of learning videos is on the learning outcomes of smk class X TITL students in basic subjects of electronic electricity which are material on the basic theory of electricity. This research was conducted on class X TITL 1 students at SMK Negeri 5 Padang. Data collection is carried out by providing pre-test and post-test questions in the form of 20 multiple-choice questions with 4 answer choices. The number of samples used in this study was 29 students. To see the effectiveness of the use of learning videos by using hypothesis test data analysis and n-gain. The results of the data calculation were obtained with a test value of 0.001 and an n-gain score of 0.69. It is known that in determining the results of the t test, namely 0.001 < 0.05, it can be concluded that there is a significant difference between the pre-test value and the post-test value. The value of the n-gain score is categorized as medium with a value of 0.69. From the t-test scores and n-gain scores, it can be concluded that there is a very significant difference in the scores before using the learning video and after using this learning video.